2002
DOI: 10.1677/joe.0.1740321
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate improves insulin sensitivity in connection with intramuscular lipid content, muscle fatty acid-binding protein, and beta-oxidation in skeletal muscle

Abstract: We investigated the effect of fenofibrate, a peroxisome proliferator-activated receptor-agonist, on insulin sensitivity including lipid metabolism in skeletal muscle. Six-week-old male Sprague-Dawley rats were divided into two groups: those fed a standard chow (control) or a fructose-rich chow (fructose-fed rats (FFRs)) for 6 weeks. FFRs were treated either with a vehicle or with 30 mg/kg per day of fenofibrate for the last 2 weeks. Insulin sensitivity (M-value) was estimated by the euglycemic hyperinsulinemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 55 publications
5
50
0
Order By: Relevance
“…Zheng et al (2015a) found that PPARα was highly expressed in the liver in yellow catfish, and fenofibrate exerted lipid-lowering activity via activation of PPARα, leading to altered expression of genes involved in lipid metabolism. Fenofibrate addition also down-regulated the mRNA levels of G6PD and 6PGD, and reduced the insulin-induced TG accumulation, in agreement with other reports (Idzior-Walus et al, 2000;Furuhashi et al, 2002). Here, GW6471 pre-treatment significantly reduced the insulin-induced up-regulation of expression of FAS, G6PD and 6PGD, further indicating that the PPARα signaling pathway is involved in the insulin-induced change of lipid metabolism in yellow catfish.…”
Section: Discussionsupporting
confidence: 91%
“…Zheng et al (2015a) found that PPARα was highly expressed in the liver in yellow catfish, and fenofibrate exerted lipid-lowering activity via activation of PPARα, leading to altered expression of genes involved in lipid metabolism. Fenofibrate addition also down-regulated the mRNA levels of G6PD and 6PGD, and reduced the insulin-induced TG accumulation, in agreement with other reports (Idzior-Walus et al, 2000;Furuhashi et al, 2002). Here, GW6471 pre-treatment significantly reduced the insulin-induced up-regulation of expression of FAS, G6PD and 6PGD, further indicating that the PPARα signaling pathway is involved in the insulin-induced change of lipid metabolism in yellow catfish.…”
Section: Discussionsupporting
confidence: 91%
“…This raises the idea that the effect of RAS blockade on adiponectin levels is, at least partly, mediated by the decrease in insulin levels, which is secondary to the effect of RAS blockade on enhancing insulin sensitivity. Although administration of thiazolidinediones, peroxisome proliferator-activated receptor (PPAR)␥ agonists, has been shown to increase adiponectin concentrations, [11][12][13] treatment with metformin, a non-PPAR␥-associated antihyperglycemic agent, or fenofibrate, a PPAR␣ agonist that has recently been shown to improve insulin sensitivity, 29 has been reported to have no effect on adiponectin concentrations in mice. 13 This indicates that the change in adiponectin concentrations is not simply a consequence of an improved metabolic phenotype and that the change in adiponectin levels is indeed (directly or indirectly) RAS blockade-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, heart FABP is considered to shuttle fatty acids from the plasma membrane to mitochondria for β-oxidation while the adipocyte FABP is considered to facilitate efflux of lipolytically-derived fatty acids (Londraville and Sidell, 1996;Coe and Bernlohr, 1998). In rat heart and muscle there is a clear correlation between fatty acid oxidation and cytosolic FABP content (Veerkamp and Vanmoerkerk, 1993;Furuhashi et al 2002).…”
Section: Intracellular Fatty Acid Binding Proteinsmentioning
confidence: 99%